Evaluasi Tingkat Kepuasan Masyarakat Terhadap Penggunaan Aplikasi DG Bankaltimtara Menggunakan Pieces Framework - Susi Febiola; Dila Seltika Canta; Elvin Leander Hadisaputro (STMIK Budi Darma, 2022)
Bankaltimtara is PT Bank Pembangunan Daerah Kalimantan Timur and North Kalimantan operating under the trade name Bankaltimtara which has a banking application named DG Bankaltimtara. And intended for all Bankaltimtara customers who have savings. DG Bankaltimtara can be installed via smartphones, such as Android or IOS. That is, it is enough just to connect to the internet network and access DG Bankltimtara, especially users at the North Penajam Paser branch, so all banking matters can be easily completed in just a matter of minutes. There are several service features provided such as balance information, account mutation information, transfers between accounts and to other banks, payments, and purchases. With the DG Bankaltimtara application, it is necessary to identify problems to find out how satisfied the community or users are with the application. One method that can be used in evaluating is to use the PIECES Framework (Performance, Information, Economic, Control, Efficiency, Service) method. Based on the PIECES method which consists of Performance, Information, Economic, Control, Efficiency, and Service to measure the level of satisfaction with the use of the DG Bankaltimtara application, the North Penajam Paser branch can be seen from each of the existing variables, to see how much satisfaction the application user has. DG Bankaltimtara in the PIECES framework method is to produce an average value of the questionnaire results of 4.46 on the likert scale with very satisfied category